Mechanism of action of Lupus anticoagulants - Arnout, J. (Hämostaseologie, 2001)
The antiphospholipid syndrome (APS) is defined as the association of antiphospholipid antibodies (aPL) with thrombosis, fetal loss or thrombocytopenia. Some aPL can be detected via coagulation assays where they present as an aspecific inhibitor termed the lupus anticoagulant (LA). Others can be measured via direct binding to cardiolipin and are termed anticardiolipin antibodies. aPL found in APS patients bind to a variety of PL-binding proteins such as beta-2-glycoprotein I (β2GPI) and prothrombin bound to PL surfaces. LA retard coagulation reactions in vitro by forming stable bivalent immune complexes on coagulation active phospholipids. These complexes have increased affinity for PL and compete with coagulation factors for the same catalytic surface. Animal experimental work has provided evidence that aPL are pathogenic. Based on similarities with heparin induced thrombocytopenia, another thrombotic syndrome, the following mechanism might be proposed. As a consequence of an initial activation, anionic PL exposed on bloodcells, endothelium or trophoblasts may promote the formation of bivalent complexes of aPL and PL-binding proteins. In this way, aPL concentrate on the cell surface, activate cellular FcγRII receptors or the complement system and induce thrombosis.
Keywords: Antiphospholipid syndrome; lupus anticoagulant; beta-2-glycoprotein I; prothrombin